Theoretically legal characteristic of legal regulation of the pipeline service in Ukraine - Довженко, Євгенія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Great importance of pipeline service determined by its significance not only for Ukrainian economy but also to ensure its existence as a whole, a vast lag of the legal framework of this kind of transport from the actual level of its development, as well as the lack of scientific attention to these problems necessitated their in-depth research. This article provides a general theoretical study of the role and place of the rules governing the operation of pipelines in the legal system of Ukraine. The author states the basic problems of legal regulation of pipelines and offers possible solutions. The main directions of further development of legislation on pipeline transport, according to the author, are as follows: elimination of pipeline transport regulations from transport regulations and its integration into the system of legal acts on energy, taking into account the relevant European experience, ensuring transparency of pipeline transport and public management in this area, as well as Ukraine’s energy security.